KEPEMIMPINAN KYAI DALAM MENGAKTUALISASIKAN MODERNISASI PENDIDIKAN PESANTREN DI PERGURUAN TINGGI (STUDI INTERAKSIONISME SIMBOLIK DI MA’HAD SUNAN AMPEL AL-‘ALY UIN MALIKI MALANG) - Pramitha, Devi (J-PAI: Jurnal Pendidikan Agama Islam, 2017)
The Kiai as the leader of the boarding school is not just to lead, but also develop curricula, create evaluation system, determine the order of the institution came to organize the life of the whole community of cottage boarding and also foster community. In this study, there are three objectives are achieved, namely: (1) obtain a description and a complete picture of the behavior of the leadership of clerics; (2) obtain a description and a complete picture of the interaction patterns clerics; and (3) obtaining a description and a complete overview of the concept of modernization of education schools in Higher EducationThis type of research is qualitative and using the case study method. Ma'had Sunan Ampel Al-`Aly selected as the research object because it is the first boarding school students in the environment PTAIN. Data obtained by interview (interview), documents (documents) and observations (observation). Spradley data analysis using a model consisting of domain analysis, analasis taxonomy, componential analysis and thematic analysis.Three results obtained, namely, (1) Conduct Yai Chamzawi leadership in MSAA UIN Maliki leads to transformational leadership; (2) The pattern of interaction Yai Chamzawi in MSAA UIN Maliki leads to the traditional leadership; and (3) The concept of modernization of education schools in universities based on the principle of al-Muhafadzatu 'ala qadimi as-salih wa al-akhdu bi al-jadidi al-aslah. So from the third conclusion above can researchers find a style of leadership clerics in MSAA UIN Maliki is Leadership Style Neo-Transformasionalisme, which is a combination of leadership styles transfomasionalisme and leadership style traditionalism based on the principle of al-muhafadzatu 'alal qadimi shalih wal akhdu bil jadidil ashlah.Keywords: Leadership of Kyai, Modernization of Islamic Boarding Scool Education, College